Nonstationary chimeras in a neuronal network - Wei, Zhouchao; Parastesh, Fatemeh; Azarnoush, Hamed; Jafari, Sajad; Ghosh, Dibakar; Perc, Matja; Slavinec, Mitja (Europhysics letters, 2018)
Chimeras are special states that are composed of coexisting spatial domains of coherent and incoherent dynamics, which typically emerge in identically coupled oscillators. In this paper, we study a network of nonlocally coupled Hindmarsh-Rose neurons that are subject to an alternating current. We show that chimera states emerge when the neurons are connected through electrical synapses. The considered model has two coexisting attractors, namely a limit cycle and a chaotic attractor, to which the dynamics converges in dependence on the initial conditions. While earlier research reported the existence of chimeras in Hindmarsh-Rose neuronal networks mainly through chemical synapses, here we show that an alternating current in an electrically coupled network can also evoke chimeras, whereby the spatial positions of coherent and incoherent domains vary with time. Remarkably, we also observe chimera states in locally coupled neurons through electrical synapses, which reduce the relaxation of nonlocallity in the coupling configuration. The existence of nonstationary chimeras is confirmed by means of a local order parameter.